2017
DOI: 10.1371/journal.pone.0186578
|View full text |Cite
|
Sign up to set email alerts
|

Self-administered Vitamin D Status Predictor: Older adults are able to use a self-questionnaire for evaluating their vitamin D status

Abstract: BackgroundThe 16-item Vitamin D Status Predictor (VDSP) questionnaire helps to identify, without resorting to a blood test, older adults with low vitamin D concentrations. Our objective was to determine whether a self-administered VDSP was concordant with the VDSP administered by a physician, and to examine the concordance of every single item of the VDSP.MethodsA total of 349 older in- and outpatients (mean, 83.2±7.2years; 59% female) were consecutively recruited in the geriatric ward of the University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“… 10 , 14 In addition to serum examinations, some studies have discussed the diagnosis of vitamin D status using a questionnaire. 4 This suggests that an invasive examination is not required to establish vitamin status, but this study focused only on the elderly. 4 Other studies have shown that serum levels offer more precise results compared to other body fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 14 In addition to serum examinations, some studies have discussed the diagnosis of vitamin D status using a questionnaire. 4 This suggests that an invasive examination is not required to establish vitamin status, but this study focused only on the elderly. 4 Other studies have shown that serum levels offer more precise results compared to other body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency occurs in various parts of the world, including in the tropics, and it occurs in both healthy and sick people. 1 , 2 Vitamin D deficiency is often found in people with a low intake of food sources of vitamin D. 3 , 4 Vitamin D is found at higher levels in fish oil and sun exposure, but not all people can consume fish oil easily, or are exposed to sunlight, considering lifestyle factors. 5 , 6 The difficulty involved in getting fish oil or vitamin D supplements is a challenge in preventing vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of the multiple environmental and genetic factors which influence vitamin D metabolism, unlike the very successful Australian public health “Breast is Best” and “Sun Smart” Campaigns, the “Holy Grail” of a similar simple public health message to ensure Vitamin D adequacy is likely to remain elusive. Perhaps consideration could be given to developing a risk calculator for vitamin D deficiency during pregnancy, infancy and childhood such as has been developed for osteoporosis (the FRAX calculator [60] for example), for Type 2 Diabetes Risk [61] and for vitamin D deficiency risk in adults, Annweiler and colleagues have recently developed an adult self-assessment tool [62]. Returning to Maine and McCredie’s “A plea is made for adequate instruction of our migrant population in the prevention of this disease” [11], given Australia’s multicultural population and highly urbanised lifestyles, and that all mothers and their babies should have access to a Maternal Child Health Nurse, there is a pressing need to develop a Maternal Child Health Vitamin D deficiency risk assessment tool, which could also be universally applied.…”
Section: Discussionmentioning
confidence: 99%
“…The second point that needs to be considered is represented by the well-known notion of pandemic proportions of hypovitaminosis D in the population of the world (4), especially in the elderly subjects (37). Therefore, the measurement of 25(OH)D assay might not be costeffective, also considering that the price of the assay in some countries is at least ten times more than 1 year of supplementations (38). In addition to this, we should also consider that apart from the side effects reported with the utilization of mega doses of vitamin D (39,40), there is no real harm with the daily, weekly or monthly doses prescribed in clinical practice (41).…”
Section: Screening For Vitamin D Status: Against (Minisola S Colangementioning
confidence: 99%
“…Finally, there are currently a number of questionnaires that correctly predict serum 25(OH)D levels in the population as a whole as well as in specific subgroup, thus rending universal screening not rewarding considering its cost (38,48).…”
Section: Screening For Vitamin D Status: Against (Minisola S Colangementioning
confidence: 99%